GST-TAT-SOD: Cell Permeable Bifunctional Antioxidant Enzyme—A Potential Selective Radioprotector. (30th May 2016) - Pan, Jianru; He, Huocong; Su, Ying; Zheng, Guangjin; Wu, Junxin; Liu, Shutao; Rao, Pingfan
Abstract : Superoxide dismutase (SOD) fusion of TAT was proved to be radioprotective in our previous work. On that basis, a bifunctional recombinant protein which was the fusion of glutathione S-transferase (GST), SOD, and TAT was constructed and named GST-TAT-SOD. Herein we report the investigation of the cytotoxicity, cell-penetrating activity, and in vitro radioprotective effect of GST-TAT-SOD compared with wild SOD, single-function recombinant protein SOD-TAT, and amifostine. We demonstrated that wild SOD had little radioprotective effect on irradiated L-02 and Hep G2 cells while amifostine was protective to both cell lines. SOD-TAT or GST-TAT-SOD pretreatment 3 h prior to radiation protects irradiated normal liver cells against radiation damage by eliminating intracellular excrescent superoxide, reducing cellular MDA level, enhancing cellular antioxidant ability and colony formation ability, and reducing apoptosis rate. Compared with SOD-TAT, GST-TAT-SOD was proved to have better protective effect on irradiated normal liver cells and minimal effect on irradiated hepatoma cells. Besides, GST-TAT-SOD was safe for normal cells and effectively transduced into different organs in mice, including the brain. The characteristics of this protein suggest that it may be a potential radioprotective agent in cancer therapy better than amifostine. Fusion of two antioxidant enzymes and cell-penetrating peptides is potentially valuable in the development of radioprotective agent.